Thermal [2+3]-Cycloadditions of trans-1-Methyl-2,3-diphenylaziridine with CS and CC Dipolarophiles: An Unexpected Course with Dimethyl Dicyanofumarate - Mlostoń, Grzegorz; Urbaniak, Katarzyna; Domagała, Małgorzata; Pfitzner, Arno; Zabel, Manfred; Heimgartner, Heinz (Helvetica chimica acta, 2009)
The thermal reaction of trans‐1‐methyl‐2,3‐diphenylaziridine (trans‐1a) with aromatic and cycloaliphatic thioketones 2 in boiling toluene yielded the corresponding cis‐2,4‐diphenyl‐1,3‐thiazolidines cis‐4 via conrotatory ring opening of trans‐1a and a concerted [2+3]‐cycloaddition of the intermediate (E,E)‐configured azomethine ylide 3a (Scheme 1). The analogous reaction of cis‐1a with dimethyl acetylenedicarboxylate (5) gave dimethyl trans‐2,5‐dihydro‐1‐methyl‐2,5‐diphenylpyrrole‐3,4‐dicarboxylate (trans‐6) in accord with orbital‐symmetry‐controlled reactions (Scheme 2). On the other hand, the reactions of cis‐1a and trans‐1a with dimethyl dicyanofumarate (7a), as well as that of cis‐1a and dimethyl dicyanomaleate (7b), led to mixtures of the same two stereoisomeric dimethyl 3,4‐dicyano‐1‐methyl‐2,5‐diphenylpyrrolidine‐3,4‐dicarboxylates 8a and 8b (Scheme 3). This result has to be explained via a stepwise reaction mechanism, in which the intermediate zwitterions 11a and 11b equilibrate (Scheme 6). In contrast, cis‐1,2,3‐triphenylaziridine (cis‐1b) and 7a gave only one stereoisomeric pyrrolidine‐3,4‐dicarboxylate 10, with the configuration expected on the basis of orbital‐symmetry control, i.e., via concerted reaction steps (Scheme 10). The configuration of 8a and 10, as well as that of a derivative of 8b, were established by X‐ray crystallography.